2015
DOI: 10.1016/j.postharvbio.2015.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Sound waves delay tomato fruit ripening by negatively regulating ethylene biosynthesis and signaling genes

Abstract: A B S T R A C TRegulation of tomato fruit ripening may help extend fruit shelf life and prevent losses due to spoilage. Here, tomato fruit were investigated whether sound treatment could delay their ripening. Harvested fruit were treated with low-frequency sound waves (1 kHz) for 6 h, and then monitored various characteristics of the fruit over 14-days at 23 AE 1 C. Seven days after the treatment, 85% of the treated fruit were green, versus fewer than 50% of the non-treated fruit. Most of the tomato fruit had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 36 publications
(53 reference statements)
1
45
0
1
Order By: Relevance
“…The respiration peaks of the "Xiaobai" and "Daliguang" apricots stored at NFT were 50and 11% of those stored at 0°C, respectively. Inhibition of ethylene production could delay fruit senescence (Kim et al, 2015;Yang, Song, Campbell-Palmer, Fillmore, & Zhang, 2013). Suppression of respiration rate and ethylene production in apricots stored at NFT could thus increase their storage time and maintain the quality.…”
Section: Changes In the Respiration Rate And Ethylene Productionmentioning
confidence: 99%
“…The respiration peaks of the "Xiaobai" and "Daliguang" apricots stored at NFT were 50and 11% of those stored at 0°C, respectively. Inhibition of ethylene production could delay fruit senescence (Kim et al, 2015;Yang, Song, Campbell-Palmer, Fillmore, & Zhang, 2013). Suppression of respiration rate and ethylene production in apricots stored at NFT could thus increase their storage time and maintain the quality.…”
Section: Changes In the Respiration Rate And Ethylene Productionmentioning
confidence: 99%
“…Our previous studies have shown that the same gene in rice may increase or decrease in expression depending on the sound frequency . In addition, there were best sound frequencies for the regulation of gene expression related to ethylene biosynthesis of tomato and ascorbic acid biosynthesis of alfalfa sprout vegetable . Moreover, a recent report suggested that four different types of cells when treated with the same sound wave condition responded differently and the expression of related genes also differed .…”
Section: Resultsmentioning
confidence: 97%
“…showed that root growth in germinating maize ( Zea mays ) seeds was directed by sound waves. Literature evidence shows that sound waves can also alter phytohormone levels via regulation of hormone synthesis‐related genes in plants . In C hrysanthemum spp.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Effects of sound wave on the cell metabolism. (Kim et al, 2015;Ermolaeva and ark., 2015;Milowska and Gabryelak, 2007;Dikilitas et al, 2016 (Ohlemiller ve ark., 1999).…”
Section: Ses Dalgalarının Etki Mekanizmalarımentioning
confidence: 99%